Inovasi dalam Manajemen SDM: Pengaruh Sinergi Motivasi dan Kompetensi terhadap Kinerja Pegawai di Industri Kepariwisataan Jawa Barat - Silviani Agustin (CV. ULIL ALBAB CORP, 2024)
This study aims to activate the influence of Competence, Motivation, and Job Satisfaction on Employee Performance in Regional Service and Tourism Companies, which is based on initial findings that employee performance in the company is not optimal. This study uses a descriptive analysis method with a population of 55 employees, where the entire population is used as respondents in the survey. The analysis techniques used include correlation analysis to measure the closeness of the relationship between variables, and path analysis to assess the direct and indirect influence of independent variables on dependent variables, with the help of SPSS 16 and Excel software. The results of the study indicate that Motivation, Competence, and Job Satisfaction of employees are in the good category and have a simultaneous influence on Employee Performance of 0.653, while 0.346 is partly influenced by other variables not included in this study. This study emphasizes the importance of developing competence and motivation in efforts to improve employee performance, and emphasizes that job satisfaction plays a significant role in influencing the performance results of Regional Service and Tourism Companies